2022
DOI: 10.21764/maeuefd.1006596
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Work-Life Balance and Organizational Commitment According to the Opinions of Primary School Teachers

Abstract: The purpose of this study it was to determine the relationship between work life balance and organizational commitment according to the opinions of teachers, working in official primary and secondary schools affiliated to the Ministry of National Education. In the study, exploratory model of correlational survey method was used. The population of the research consists of primary education teachers working in Antalya's Muratpaşa, Kepez, Konyaaltı, Aksu and Döşemealtı districts in the 2019/2020 academic year. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Teachers' perceptions of dedication to the profession are high in all dimensions, including commitment to the profession, devotion to students, and selfless work. Ekinci (2012), Aytekin (2016), Alim (2019), and Ertürk (2021) also concluded that teachers have high devotion to the profession. In this context, the results of this study are similar to the results of the studies in the literature.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Teachers' perceptions of dedication to the profession are high in all dimensions, including commitment to the profession, devotion to students, and selfless work. Ekinci (2012), Aytekin (2016), Alim (2019), and Ertürk (2021) also concluded that teachers have high devotion to the profession. In this context, the results of this study are similar to the results of the studies in the literature.…”
Section: Conclusion and Discussionmentioning
confidence: 99%